The role of financial technology in ZISWAF (Zakat, Infak, Alms and Wakaf) collection - Dwi Vita Lestari Soehardi (Institute of Computer Science (IOCS), 2023)
Indonesia, which has a large Muslim population, has a lot of potential for Zakat, Infak, Sedekah dan Wakaf (ZISWAF). After the pandemic, there have been changes that have made people adaptive to technology. This rapidly developing technological development also affects services at Islamic financial institutions. One type of Financial Technology in Indonesia is Digital Payment or digital platforms such as e-commerce, Apps, Social Media, and Online Payment Channels. This research method uses a literature study or library research using secondary data sources. The way researchers conduct research is descriptive using a qualitative approach. The availability of Fintech services at ZISWAF collection institutions provides a special attraction for the community. The use of digital payment services will certainly provide convenience and comfort for the community in implementing the Halal Lifestyle. Digital literacy in technology is the main key to implementing fintech-based Islamic philanthropic fund management. In the current digital era, fintech plays a role in positively impacting ZISWAF collecting.